Estudio de la escarificación en la germinación del barbasco clavija sp. mediante cinco métodos - Vega Jaramillo, Vanessa Lizbeth (2006)
In the Agricultural Sciences Faculty, of the University of Machala, it was developed the effect that has the scarification in the germination of the barbasco's seeds also in the development of the little plants. The methods used were: chemical, hormonal, bioestimulants and natural subtances. The objectives proposed in this essay were: 1. To evaluate the effects of the scarification in the barbasco's germination; 2. To determine the method and the dose of more effect in the postmaduration of embryos as well as in the germination and growth of the little plants; 3. To obtain little barbasco's plants. The experimental design adopted for the analysis and interpretation of the results was completely randomized, with 30 repetitions; in which the following treatments were studied: Gilberilic acid of 500 and 1000 parts per million (ppm), Sulfuric acid to 1 %, 3 % and 6 %, Hydrochloric Acid to 1%, 3% and 6%, Ergostim 50 % to 100 %; water 40º C to 60º C and absolute witness. The statistical analyses evidenced that the gilberilic acid in dose of 1000 ppm and 500 ppm jointly with the ergostim to 100 % gave they were very effective as for reducing the days of the germination of the barbasco. The seeds tried with the hormonal treatment germinated to the 18 and 23 days (gilberilic acid of 1000 ppm and 500 ppm), while to the 19 days the seeds tried with ergostim to 100 % germinated. The best result as for germination percentage registered with gilberilic acid of 1000 ppm with 83 %, in order of merit they follow the treatments of gilberilic acid of 500 ppm and it dilutes respectively 60º C with 63,25 % and 60 %, these differed significantly of the absolute witness. The chemical scarificatión with sulfuric acid to 3 % and 6 % was fitotóxica for the seeds giving a very low percentage and germinative vigor as a result. The smallest number of days until the formation of five true leaves registered with the scarificatión tried with gilberilic acid 1000 ppm with 70 days, followed by 72 days those that were obtained with ergostim to 100 %. The biggest height reached by the litte plants was given in the seeds tried with ergostim to 100 % and gilberilic acid 1000 ppm with 4,8 cm; this last one in dose of 500 ppm reached 4,3 cm.